Effect of vitrification on the microRNA transcriptome in mouse blastocysts. - Xueming Zhao; Haisheng Hao; Weihua Du; Huabin Zhu (PLoS ONE, 2015)
Vitrification is commonly used in the cryopreservation of mammalian blastocysts to overcome the temporal and spatial limitations of embryo transfer. Previous studies have shown that the implantation ability of vitrified blastocysts is impaired and that microRNAs (miRNAs) regulate the critical genes for embryo implantation. However, little information is available about the effect of vitrification on the miRNA transcriptome in blastocysts. In the present study, the miRNA transcriptomes in fresh and vitrified mouse blastocysts were analyzed by miRNA Taqman assay based method, and the results were validated using quantitative real-time PCR (qRT-PCR). Then, the differentially expressed miRNAs were assessed using the Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) databases. Overall, 760 known mouse miRNAs were detected in the vitrified and fresh mouse blastocysts. Of these, the expression levels of five miRNAs differed significantly: in the vitrified blastocysts, four miRNAs (mmu-miR-199a-5p, mmu-miR-329-3p, mmu-miR-136-5p and mmu-miR-16-1-3p) were upregulated, and one (mmu-miR-212-3p) was downregulated. The expression levels of all miRNAs measured by the miRNA Taqman assay based method and qRT-PCR were consistent. The four upregulated miRNAs were predicted to regulate 877 candidate target genes, and the downregulated miRNA was predicted to regulate 231 genes. The biological analysis further showed that the differentially expressed miRNAs mainly regulated the implantation of embryos. In conclusion, the results of our study showed that vitrification significantly altered the miRNA transcriptome in mouse blastocysts, which may decrease the implantation potential of vitrified blastocysts.